Multi-Element Analysis of Gold Ore Mill Heads by Instrumental Neutron Activation Technique (Journal of Science and Technology, 2016)
Instrumental neutron activation analysis by Americium-Beryllium radioisotope neutron source has been employed for the multi-element analysis of gold ore mill heads from five different cites of the State Gold Mine at Prestea in Ghana. Gold was identified in ppm levels. The major elements identified were Al, Na and K. These were found to be common to all the five sites. The minor elements found were Cu. As. Mn. Ca, Sb. Mg, V and Br Some of the minor elements were however absent at some of the sites. The following elements. Fe. Rb. Sr and Zr were also identified but could not be qualified.